2014
DOI: 10.1093/pcp/pcu124
|View full text |Cite
|
Sign up to set email alerts
|

The Auxin Sl-IAA17 Transcriptional Repressor Controls Fruit Size Via the Regulation of Endoreduplication-Related Cell Expansion

Abstract: Auxin is known to regulate cell division and cell elongation, thus controlling plant growth and development. Part of the auxin signaling pathway depends on the fine-tuned degradation of the auxin/indole acetic acid (Aux/IAA) transcriptional repressors. Recent evidence indicates that Aux/IAA proteins play a role in fruit development in tomato (Solanum lycopersicum Mill.), a model species for fleshy fruit development. We report here on the functional characterization of Sl-IAA17 during tomato fruit development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 36 publications
0
53
1
Order By: Relevance
“…On the other hand, the analysis of loss-of-function mutants has so far failed to reveal robust mutant phenotypes in Arabidopsis, suggesting extensive genetic redundancy among members of the family (Remington et al, 2004;Overvoorde et al, 2005;reviewed in Reed, 2001). This is in contrast to the situation in tomato (Solanum lycopersicum) where several loss-of-function alleles or antisense constructs produce a robust phenotype suggesting that there is less redundancy in this species (Wang et al, 2005;Chaabouni et al, 2009;Bassa et al, 2012;Deng et al, 2012;Su et al, 2014).…”
Section: Aux/iaa and Arf Genes Act Downstream Of Scf Tir1/afbscontrasting
confidence: 71%
“…On the other hand, the analysis of loss-of-function mutants has so far failed to reveal robust mutant phenotypes in Arabidopsis, suggesting extensive genetic redundancy among members of the family (Remington et al, 2004;Overvoorde et al, 2005;reviewed in Reed, 2001). This is in contrast to the situation in tomato (Solanum lycopersicum) where several loss-of-function alleles or antisense constructs produce a robust phenotype suggesting that there is less redundancy in this species (Wang et al, 2005;Chaabouni et al, 2009;Bassa et al, 2012;Deng et al, 2012;Su et al, 2014).…”
Section: Aux/iaa and Arf Genes Act Downstream Of Scf Tir1/afbscontrasting
confidence: 71%
“…1,2 Unlike the situation in the model plant Arabidopsis where the functional significance of Aux/ IAAs was mainly gained by the analysis of gain-of-function mutants, uncovering the function in planta of tomato Aux/IAAs was mainly achieved through the characterization of downregulated lines. 3 and refs herein; [4][5][6][7] In particular, we have recently shown that down-regulation of Sl-IAA17 gene in tomato results in fruits with higher weight and thicker pericarp, probably as a result of enhanced cell expansion linked to an increased endoreduplication rate. 7 We report here on additional phenotypes related to fruit ripening traits uncovered in these Sl-IAA17 downregulated lines.…”
mentioning
confidence: 89%
“…3 and refs herein; [4][5][6][7] In particular, we have recently shown that down-regulation of Sl-IAA17 gene in tomato results in fruits with higher weight and thicker pericarp, probably as a result of enhanced cell expansion linked to an increased endoreduplication rate. 7 We report here on additional phenotypes related to fruit ripening traits uncovered in these Sl-IAA17 downregulated lines.…”
mentioning
confidence: 89%
See 2 more Smart Citations